Upaya Perlindungan Psikologis Anak Broken Home menurut Ibnu Qayyim: Studi Kasus di Kelurahan Tanjung Selamat, Kecamatan Padang Tualang - Jian Alfarisi Sahuli; Uswatun Hasanah (AL-SULTHANIYAH, 2026)
The increasing incidence of broken-home families in Tanjung Selamat Village, Padang Tualang District, has contributed to a range of psychological problems among children. This study aims to analyze the psychological condition of children from broken-home families in Tanjung Selamat Village, Padang Tualang District, and to examine psychological protection efforts from the perspective of Ibn Qayyim. This research employed a qualitative descriptive approach. Primary data were collected through in-depth interviews with members of the local community in Tanjung Selamat Village, while secondary data were obtained from relevant documents and literature. The findings reveal that children from broken-home families experience various psychological difficulties, including feelings of insecurity, depression, and challenges in social interaction. From Ibn Qayyim's perspective, psychological protection can be achieved through strengthening one's relationship with Allah (SWT), cultivating patience, managing emotions effectively, developing psychological resilience, fostering healthy communication, providing affection and a sense of security, introducing positive parental substitute figures, and protecting children from harmful environments. These protective measures should be implemented continuously through collaborative efforts, with the family serving as the primary agent in supporting children's psychological recovery and healthy development.